Prenatal Diagnosis of Rare Familial Unbalanced Translocation of Chromosomes 7 and 12 - Berrin Tezcan; Foteini Emmanouella Bredaki (Case Reports in Obstetrics and Gynecology)
Case Details. We report rare familial unbalanced translocation of chromosomes 7 and 12, which was diagnosed prenatally at 20+3 weeks of gestation. Woman’s partner had been tested in the past and was found to be a carrier of a balanced translocation; his karyotype showed a balanced reciprocal translocation of 46, XY, t(7;12)(q34;q24,32). Partner’s brother had an unbalanced form of the translocation with severe learning disability. The diagnosis of the anomaly was based on two- and three-dimensional ultrasound and microarray analysis. Ultrasonography findings included fetal microcephaly and alobar holoprosencephaly, dysmorphic face (flat occiput, absent nasal bone, microphthalmia, hypotelorism, and single nostril), and hyperechogenic bowel. Genome-wide array analysis and cytogenetic results from the amniotic fluid showed unbalanced translocation in chromosomes 7 and 12 with deletion of an approximately 16.5 Mb and a duplication of 6.1 Mb, respectively, Arr 7q34q36.3(142,668,576-159,161,648)x1,12q24.32q24.33(127,708,720-133,777,560)x3, karyotype (der (7) t(7;12) (q34;q24)pat). This unbalanced translocation was due to the segregation of the father’s balanced translocation. In this particular case, the recurrence of an unbalanced translocation in the subsequent pregnancies is estimated to be 20%. Understanding the individuals’ phenotype in association with the gain and loss of copy number is important and can further provide us with information on that particular region of the named chromosomes.